Effect of mercury (HG) on some biological parameters of channa punctatus - Gupta, Yogesh; Kumar, Pravesh (International Journal of Biological Research, 2016)
Freshwater fish, channa punctatus caught from Yamuna river studied for toxicity and biological parameters. In the present study short-term (96 hr) toxicity of mercury in relation to estimation of hematological test for channa punctatus. The control fishes showed mean value of 75.00 g/dL for hemoglobin. The fishes were exposed to sub- lethal concentration of mercuric chloride showed the hemoglobin mean values of 67.2, 50.8, 42.6 and 29.2 g/dL hemoglobin at 0.02, 0.04, 0.06, 0.08, and 0.10 ppm treatment respectively. The values for treatments showed a significant decrease when compared to the control (P-0.05).The heavy metals has a direct effect on the 96-hr LC50 values of the respective heavy metals and the susceptibility of fish.